WHEAT FLOUR PRESERVATION BY MEANS OF PACKAGING AND ITS STATISTICAL EVALUATION (Biological Sciences - PJSIR, 2002)
The wheat flour (atta) stored in  conventional  packaging  materials  i.e. jute  (gunny), cloth, woven  polyethylene  threads  bags which were in contact with air deteriorated more quickly than the wheat flour stored in  air tight polyethylene  acetate bags containing free oxygen absorber  (FOA).  The  colour, taste , texture,  flavour , acidity, organoleptic  evalation,  insect and bacterial count remained acceptable for two months  in  polyethylene -acetate  coated  impermeable  bags  containi ng  FOA and insect infestation was zero. These changes were due to anaerobic fermentation of starch in wheat  flour.  The statistical  presentation  of the data  has been  carried  out.